Research integrity and responsible conduct of research - Nichols-Casebolt, Ann, 1949- (New York ; Oxford : Oxford University Press, 2012)
With useful case studies, sample protocols, and take-home points, this is a succinct yet valuable guide to the ethical practice of research for social work students, faculty, and agency-based staff.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Social sciences -- Research -- Moral and ethical aspects; Social sciences -- Methodology -- Moral and ethical aspects